(untitled) (Dhaka University Journal of Biological Sciences, 2020)
The susceptibility of different stored pulses infested by Callosobruchus chinensis L. (Coleoptera: Bruchidae) was observed in three varieties of stored pulses i.e. gram (Cicer arietnum L.), pea (Pisum sativum L.) and mung (Vigna radiata L.) during April, 2017 to May, 2018. The longest incubation-, larval- and pupal period of pulse beetle were in gram 5.4 ± 0.29, 12.6 ± 0.25, 5.5 ± 0.32 days, respectively and the shortest were in mung 4.6 ± 0.25, 11.3 ± 0.28, 4.2 ± 0.19 days, respectively. The shortest developmental period of pulse beetle was 20.1 ± 0.46 days in mung. The incubation-, larval-, pupal- and total developmental period of pulse beetle varied significantly between the pulse beetle grown in gram and mung (p < 0.05). The highest longevity and fecundity were in gram, 8.2 ± 0.33 days and 70.2 ± 7.53, respectively. The fecundity did not vary significantly in different stored pulses (p > 0.05). The longevity and number of adults emerged varied significantly (p < 0.05) between the gram and pea. The number of male emerged did not vary significantly (p > 0.05) between the different stored pulses and the number of female emerged varied significantly (p < 0.05) between gram and pea, pea and mung. The experiment revealed that pulse beetle preferred smooth coated and large size seeds to oviposit. Pea was found to be most resistant to attack by C. chinensis L. whereas mung was more susceptible than gram and pea. Dhaka Univ. J. Biol. Sci. 29(1): 19-25, 2020 (January)